2020
DOI: 10.1039/c9fo02517k
|View full text |Cite
|
Sign up to set email alerts
|

Fermented blueberry pomace ameliorates intestinal barrier function through the NF-κB-MLCK signaling pathway in high-fat diet mice

Abstract: The barrier-improving functions of fermented blueberry pomace (FBP) and its potential mechanism were investigated in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 65 publications
1
43
0
Order By: Relevance
“…Intake of high-fat foods has been reported to induce changes in the intestinal flora, thereby increasing intestinal permeability, a significant factor in the onset of Crohn’s disease [ 35 ]. NF-κB, a critical transcriptional regulator of the inflammatory response, is also a crucial factor in intestinal inflammation [ 36 ] and is activated by various stimuli, including inflammatory cytokines such as TNF and pathogen-derived molecules [ 37 ]. In the present study, we demonstrated that administration of Lactobacillus plantarum strains ATG-K2 and ATG-K6 reduced HFHF diet-induced small-intestine inflammation by regulating pro-inflammatory cytokines in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Intake of high-fat foods has been reported to induce changes in the intestinal flora, thereby increasing intestinal permeability, a significant factor in the onset of Crohn’s disease [ 35 ]. NF-κB, a critical transcriptional regulator of the inflammatory response, is also a crucial factor in intestinal inflammation [ 36 ] and is activated by various stimuli, including inflammatory cytokines such as TNF and pathogen-derived molecules [ 37 ]. In the present study, we demonstrated that administration of Lactobacillus plantarum strains ATG-K2 and ATG-K6 reduced HFHF diet-induced small-intestine inflammation by regulating pro-inflammatory cytokines in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, fermented blueberries increased sIgA level by improving gut microbiota and SCFAs production [ 85 ]. Moreover, this product has been shown to counteract intestinal inflammation by the reduction of TNF-α and myeloperoxidase and inducing interleukin (IL-10) production and improved gut barrier function and immunity by regulating NF-κB/myosin light-chain kinase (MLCK) signaling [ 87 ] and the overexpression of MLCK results in gut barrier permeability and dysfunction [ 87 , 88 ].…”
Section: Fermented Berriesmentioning
confidence: 99%
“…The metabolic bacteria associated with SCFAs were Bifidobacterium and Akkermansia, among others, which could reduce the colon pH, inhibit the growth of intestinal pathogenic bacteria, participate in the synthesis of cholesterol, and provide energy for colonic epithelial cells. 32,33 This result shows that a certain dose of stachyose has the function of protecting colon tissues and promoting the growth of epithelial cells. Simultaneously, we found that the relative abundance of acetic acid-producing Blautia was significantly increased after stachyose intake.…”
Section: Discussionmentioning
confidence: 84%